2019
DOI: 10.1177/1753466619868935
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary optimized practice in the management of pulmonary sarcoidosis

Abstract: Pulmonary sarcoidosis is the most common form of sarcoidosis, accounting for the initial presentation in over 70% patients and with eventual presence in 90% of patients with sarcoidosis. However, the course of the disease is often unpredictable; its manifestations can be highly variable and its treatment may not be effective in all patients. As such, the optimized treatment of pulmonary sarcoidosis often requires a thoughtful personalized approach with the need to get the patient involved in decisions of manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 66 publications
0
19
0
1
Order By: Relevance
“…Given that prescription of non‐corticosteroid immunomodulatory drugs was by the co‐managing medical specialist, recommendations were not built around the dosing of conventional or biologic immunosuppressive drugs. As a general principle in managing inflammatory disease, cessation of immunomodulatory therapy is considered after a period of quiescence 23‐25 . The Working Group recommended that after inflammation was inactive for 24 months, cessation of the systemic immunosuppressive drug could be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Given that prescription of non‐corticosteroid immunomodulatory drugs was by the co‐managing medical specialist, recommendations were not built around the dosing of conventional or biologic immunosuppressive drugs. As a general principle in managing inflammatory disease, cessation of immunomodulatory therapy is considered after a period of quiescence 23‐25 . The Working Group recommended that after inflammation was inactive for 24 months, cessation of the systemic immunosuppressive drug could be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Corticosteroids have been used for decades as first line treatment of cardiac sarcoidosis (Aryal and Nathan, 2019;Grutters and van den Bosch, 2006). Steroid-sparing immunomodulators have been used or tested as second line treatment for refractory disease.…”
Section: Immunosuppressionmentioning
confidence: 99%
“…Presently, oral corticosteroids (e.g., prednisolone) are recommended as the first-choice therapy for sarcoidosis [92]. This recommendation is mainly based on expert opinion and a few relatively small observational studies and low-quality randomized trials from over 20 years ago [91,93]. Older studies have demonstrated that corticosteroids lead to an improvement in lung function, especially in patients with initial severe impairment of lung function [94,95].…”
Section: Disease Modifying-treatmentmentioning
confidence: 99%
“…Disease relapse occurs in over 30% of patients after discontinuation of corticosteroids. Furthermore, due to the lack of larger randomized trials the optimal dosage and duration of treatment remains unclear [93].…”
Section: Disease Modifying-treatmentmentioning
confidence: 99%
See 1 more Smart Citation